Contemporary Prints from the Federal Republic of Germany. - Grochowiak, Thomas (Stuttgart : Institut für Auslandsbeziehungen, 1978)
Albers, Josef ; Alt, Otmar ; Antes, Horst ; Asmus, Dieter ; Bayrle, Thomas ; Bubenik, Gernot ; Damke, Bernd ; van Dülmen, Gerd ; Fruhtrunk, Günter ; Geiger, Rupprecht ; Janssen, Horst ; Kalinowski, Horst Egon ; Klapheck, Konrad ; Krieg, Dieter ; Kriwet, Ferdinand ; Leissler, Arnold ; Lenk, Kaspar Thomas ; Mack, Heinz ; Mavignier, Almir ; Meckseper, Friedrich ; Monkiewitsch, Lienhard von ; Nagel, Peter ; Neuenhausen, Siegfried ; Nöfer, Werner ; Palm, Joachim ; Petrick, Wolfgang ; Pfahler, Georg Karl ; Piene, Otto ; Quinte, Lothar ; Schultze, Bernard ; Schwarz, Rainer ; Sorge, Peter ; Störtenbecker, Nikolaus ; Uecker, Günther ; Ullrich, Dietmar ; Vostell, Wolf ; Wilding, Ludwig ; Wintersberger, Lambert Maria ; Wunderlich, Paul
biografie
Contemporary Prints from the Federal Republic of Germany, Institute for Foreign Cultural Relations, Stuttgart, Exhibition, 1978/79
Engels
kunstcatalogus
Keywords: Duitsland